Morphosyntactic Variation in Medieval Celtic Languages Corpus-Based Approaches - Lash, Elliott; Qiu, Fangzhe; Stifter, David (Trends in Linguistics. Studies and Monographs [TiLSM], 2020)
This book showcases the state of the art in corpus-based linguistic analysis of Celtic languages (specifically, Old/Middle Irish, Middle Welsh, and Cornish). It explores corpus approaches to morphosyntactic variation in the medieval Celtic languages and, for the first time, situates them in the broader field of computational and corpus linguistics by providing descriptions of tools for processing the data to create electronic corpora.